2005
DOI: 10.1016/j.bbamcr.2005.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast homologue of Tip41-like proteins regulates type 2A phosphatases and responses to nitrogen sources

Abstract: A fission yeast (Schizosaccharomyces pombe) gene encoding a member of the TIP41-like protein family was identified and characterized. Deletion of the fission yeast tip41 gene leads to slower growth when ammonium chloride is the nitrogen source, but the growth rate is not affected when adenine is the nitrogen source. The tip41 mutant cells also enter the G1 phase of the cell cycle earlier than wild-type cells in response to nitrogen starvation. Overexpression of tip41(+) causes cell death, spherical cell morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…4 A, b, Right), suggesting the action of NS4A behaved at least in part like that of Tip41 protein. This premise is supported by the fact that Tip41 is a negative regulator of Tor1 (57,58). Additional experiments are needed to verify this possibility.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…4 A, b, Right), suggesting the action of NS4A behaved at least in part like that of Tip41 protein. This premise is supported by the fact that Tip41 is a negative regulator of Tor1 (57,58). Additional experiments are needed to verify this possibility.…”
Section: Discussionmentioning
confidence: 57%
“…Our results described here are largely in agreement with that report. In addition, we showed that NS4A confers its cytopathic effects specifically through Tor1 and Tip41, which are the human equivalents of Tsc1 and Tip41 proteins (58,78). It would be interesting to examine further whether the other six ZIKV proteins exert an effect similar to that of NS4A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tor2-depleted fission yeast cells exhibit a phenotype very similar to that of wild-type cells starved for nitrogen, including arrest at the G1 phase of the cell cycle, induction of nitrogen-starvation-specific genes, and entrance into the sexual development pathway, which is in contrast to the failure of tor1 mutants to initiate sexual development or arrest in G1 under nitrogen starvation (Matsuo et al, 2007;Weisman et al, 2007). The fission yeast Tip41, a regulator of TAP42 required for Tor regulation, also plays a partial role in cellular responses to nitrogen nutrient conditions through regulation of type 2A phosphatase activity (Fenyvuesvolgyi et al, 2005). The tip41 mutant cells also enter the G1 phase earlier than wild-type cells in response to nitrogen starvation, while overexpression of tip41(+) causes cell death, spherical cell morphology and blocks the shift to the G1 phase upon nitrogen starvation (Fenyvuesvolgyi et al, 2005).…”
mentioning
confidence: 97%